2023
DOI: 10.1002/vms3.1109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the in vitro and in vivo effect of liposomal doxorubicin along with oncolytic Newcastle disease virus on 4T1 cell line: Animal preclinical research

Abstract: Background: Breast cancer is one of the most common malignancies in women, with one in 20 globally. Oncolytic viruses have recently been the first step in the biological treatment of cancer, either genetically engineered or naturally occurring. They increase specifically inside cancer cells and destroy them without damaging normal tissues or producing a host immune response against tumour cells or expressing transgenes. One of the most known members of this family is the Newcastle disease virus (NDV), a natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Iron overload disrupts the body's iron homeostasis, increasing extracellular nontransferrin‐bound iron and intracellular labile iron pool. This increase in iron levels leads to the production of reactive oxygen species by the Fenton and Haber–Weiss reaction, which subsequently induces oxidative damage to vital components of the cells 11,12 . This cellular injury can cause serious complications such as heart and renal failure, immune system disorders, growth retardation, and liver disease 13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron overload disrupts the body's iron homeostasis, increasing extracellular nontransferrin‐bound iron and intracellular labile iron pool. This increase in iron levels leads to the production of reactive oxygen species by the Fenton and Haber–Weiss reaction, which subsequently induces oxidative damage to vital components of the cells 11,12 . This cellular injury can cause serious complications such as heart and renal failure, immune system disorders, growth retardation, and liver disease 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…This increase in iron levels leads to the production of reactive oxygen species by the Fenton and Haber–Weiss reaction, which subsequently induces oxidative damage to vital components of the cells. 11 , 12 This cellular injury can cause serious complications such as heart and renal failure, immune system disorders, growth retardation, and liver disease. 13 , 14 In low‐resource countries, blood transfusions with concomitant administration of iron chelators, such as Deferoxamine, L1, and Deferasirox (DFX) medications, are the most common treatment for patients with major thalassemia.…”
Section: Introductionmentioning
confidence: 99%
“…A lentogenic strain of NDV, called LaSota, was used to determine the oncolytic nature and efficacy of this virus in combination with doxorubicin in TNBC. The in vitro results showed that this NDV strain could replicate in and cause the cytolysis of 4T1 cancer cells in a dose-dependent manner [ 159 ]. When tested in a 4T1 syngeneic mouse model, the virus was administered at various hemagglutination unit (HAU) doses from 32 to 128, with one group featuring a combination with doxorubicin at 64 HAUs.…”
Section: Preclinical Ovs For Tnbcmentioning
confidence: 99%
“…The LaSota strain of NDV can selectively bind to the membrane of human tumor cells and enter the cytoplasm via endocytosis, resulting in apoptosis and DNA fragmentation of tumor cells [ 12 ]. In NDV-treated mouse tumors, the expression levels of P21, P27, and P53 genes were increased, while the expression levels of CD34, integrin α 5, VEGF, and VEGF-R genes were decreased [ 12 ]. ROS production and apoptosis pathways were reported to be stimulated by NDV in these mouse models.…”
Section: Introductionmentioning
confidence: 99%